STUDENTS"™ ERRORS IN SPEAKING DESCRIPTIVE TEXT - Pratama, Yogi; Sartika, Dewi; Asmara, Rekha (Journal of English Education Program, 2022)
To speak English fluently is a challenging ability for language learners in learning English. But, speech errors tend to cause students speaking difficulties. The point of this study was to describe the kinds of errors made by tenth-grade students at SMAN 1 Tanjung Lubuk when reciting descriptive text. This was a qualitative investigation. The study focused on SMA Negeri 1 Tanjung Lubuk's tenth-grade students in Academic 2019/2020. Recording or videotaping students' speaking performances, as well as English instructor scores, served as the research instrument in this study. The following steps were taken to analyze the data: a) data collection, b) error identification, c) categorization into error categories, d) statement of the relative frequency of error types, and e) identification of the target language's areas of difficulty, and f) therapy. The study's findings revealed that grammatical and speech errors were the most common types of speaking errors.